2022
DOI: 10.3390/cancers14092248
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Role of Interepithelial Mucosal Mast Cells in the Context of Intestinal Adenoma-Carcinoma Progression

Abstract: Mast cells (MCs) are crucial players in the relationship between the tumor microenvironment (TME) and cancer cells and have been shown to influence angiogenesis and progression of human colorectal cancer (CRC). However, the role of MCs in the TME is controversially discussed as either pro- or anti-tumorigenic. Genetically engineered mouse models (GEMMs) are the most frequently used in vivo models for human CRC research. In the murine intestine there are at least three different MC subtypes: interepithelial muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…In tumors, they may contribute to tumor growth, angiogenesis, and immune suppression. Based on the data published so far, it was concluded that IEMCs appear only in pathological conditions (28).…”
Section: Discussionmentioning
confidence: 99%
“…In tumors, they may contribute to tumor growth, angiogenesis, and immune suppression. Based on the data published so far, it was concluded that IEMCs appear only in pathological conditions (28).…”
Section: Discussionmentioning
confidence: 99%
“…Our data show important chemotactic effects of LPI on a cell culture that renders cells closely resembling mucosal MCs [ 47 ]. Although MCs with a connective tissue phenotype (i.e., expressing tryptase) have been found to be associated with tumors and tumor-associated MCs seem to suffer important changes to their phenotype due to conditions prevalent in the tumor environment [ 29 ], mucosal-type MCs have been importantly related to colon cancer [ 48 ] and to adenoma–carcinoma progression [ 49 ]. Future research should be conducted to analyze the effects that the LPI/GPR55 axis exerts on connective tissue MCs and whether this is related to the pro- and anti-tumoral roles that have been described for MCs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to microbiome-based biomarkers, there is also an emerging interest in mast cells (MCs) [ 82 , 83 , 84 , 85 ], microRNAs (miRNAs) [ 86 , 87 ], imaging, and machine-learning models [ 42 ] as non-invasive disease diagnostic and prognostic biomarkers that promise to shape the future of precision medicine. Sometimes, there is a crosstalk between the human microbiota and other genetic or chemical biomarkers.…”
Section: The Rationale For Microbiome-based Disease Biomarkersmentioning
confidence: 99%